Religious Unification, Regional Divergence: Exploring Multifaceted Linguistic Practices and Identities among the Israeli Druze and the Druze Community in the Golan Heights - Kheir, Eve Afifa (Druze Studies Journal, 2024)
This study delves into a comparative analysis of language and identity within two distinct Druze communities: those residing in the Golan Heights, who transitioned from Syrian to Israeli governance post the 1967 War, and their counterparts within Israel proper. Both communities find themselves situated as ’sandwiched’ communities, with the Golan Druze caught between Israeli and Syrian nationalisms and the Israeli Druze positioned amid the dynamics of Israel and the Arabs. Given the fluid nature of collective identities, which are subject to continuous shaping by sociopolitical influences within and beyond state boundaries, this study focuses on two pivotal political debates in each community during the fieldwork period. The Israeli Druze community is primarily concerned with the Israeli-Nation State law controversy. Meanwhile, the Golan Heights Druze community is grappling with the intensifying and widely publicized speculation regarding secret negotiations between Assad’s regime and Israel, which suggests that the Golan was sold to Israel rather than being a result of a ’lost war.’ This study explores how these debates gradually shape the collective identities of the respective communities. The research illuminates how navigating between opposing forces leads to the emergence of novel national identities and linguistic variations within these ’sandwiched’ contexts.